PROOF
x=1; therefore, x^2=1
x^2-1=x-1
(x-1)(x+1)=x-1
x+1=1
2=1
Did that blow your mind or what?
x=1; therefore, x^2=1
x^2-1=x-1
(x-1)(x+1)=x-1
x+1=1
2=1
Did that blow your mind or what?
Follow along with the video below to see how to install our site as a web app on your home screen.
Note: This feature may not be available in some browsers.
PROOF
x=1; therefore, x^2=1
x^2-1=x-1
(x-1)(x+1)=x-1
x+1=1
2=1
Did that blow your mind or what?
No, not really. Fact is, 2 does not equal 1 and 1 does not equal 2. Goofy math = 1, and I suppose it follows that 2= goofy math. So goofy math=goofy math.
By golly, you are correct.
PROOF
x=1; therefore, x^2=1
x^2-1=x-1
(x-1)(x+1)=x-1
x+1=1
2=1
Did that blow your mind or what?
But I proved it mathematically. Is there a flaw in my proof?